The transnational sphere of justice: disability praxis and the politics of impairment - Soldatic, Karen (Routledge, 2013)
In this paper, my aim is to elaborate disability movement praxis so that transnational struggles for justice over the production of impairment emerging from the Global South can be represented within the transnational frame of disability politics. The paper seeks to explore the potential of deepening socio-political understandings of impairment as a means to radically democratize disability movement politics at the transnational scale to encompass pluralist, yet subaltern, collective claims for justice. I am guided by the question: if impairment is the place that makes visible invisible debts, can the global disability rights movement begin a process of re-identification to open the boundaries of disability justice claims and develop a strategic orientation which recognizes those collective justice claims for geopolitically produced impairments?